Microeconomics - Bernheim, B. Doughlas (McGraw-Hill, 2012)
Bernheim and Whinston’s Microeconomics focuses on the core principles of the intermediate microeconomic course: individuals and firms making decisions, competitive markets, and market failures. An accessible text that does not require knowledge of calculus, Microeconomics utilizes examples and integrates topics that will stimulate and motivate students.